The current state and potential innovation of fetal cardiac MRI - Udine, Michelle; Loke, Yue-Hin; Goudar, Suma; Donofrio, Mary T.; Truong, Uyen; Krishnan, Anita (Frontiers in Pediatrics, 2023)
Fetal cardiovascular cardiac MRI is a rapidly evolving form of diagnostic testing with utility as a complementary imaging modality for the diagnosis of congenital heart disease and assessment of the fetal cardiovascular system. Previous technical limitations without cardiac gating for the fetal heart rate has been overcome with recent technology. There is potential for future novel useutility of fetal electrocardiography for direct cardiac gating. In addition to anatomic assessment, innovative technology has allowed for assessment of blood flow, 3D datasets, and 4D flow, providing important insight into fetal cardiac cardiovascular physiology. Despite remaining technical barriers, with increased use of fCMR worldwide, it will become an important clinical tool to improve the prenatal care of fetuses with CHD. success (17,18). There are preliminary reference ranges for late gestation human fetuses that are consistent with measurements made in fetal lambs in prior studies(17). PC-MRI has been used in combination with oximetry measurements to show many expected changes in fetal circulatory physiology in fetuses with CHD including a reduction in ascending aortic flow and increase in flow across the main pulmonary artery and ductus arteriosus in fetuses with hypoplastic left heart syndrome(19).Limitations to this technique include vulnerability to movement artifact earlier in gestation, only